The The Relationship Between Gadget Use Behavior and Emotional Mental Disorders in Children in Surakarta - Asy Syifa; Tanjung Anitasari Indah Kusumaningrum (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Excessive use of digital devices has been significantly associated with adverse emotional and psychological outcomes in children, including heightened levels of anxiety and depressive symptoms. In line with these global findings, recent data from Surakarta, Indonesia, indicate that approximately 5.1% of children are affected by emotional mental disorders. The aim of this study was to analyze the relationship between gadget use and emotional mental disorders in children in Surakarta. Method: This study employed a cross-sectional design involving 139 children aged 4—5 years as observational subjects. Purposive sampling was conducted in August 2024. Data were collected using two questionnaires completed by the children’s parents: one assessing gadget use behavior, and the other evaluating emotional and behavior difficulties based on the parent-report of the Strengths and Difficulties Questionnaire (SDQ). Data analysis was conducted using Fisher’s exact test. Results: The findings indicate that 76.3% of children exhibited what was categorized as appropriate gadget use, defined in this study as a total score ranging from 1 to 38 on the parental questionnaire. Additionally, 77% of the children scored within the normal range on the Difficulties Scale (indicating no significant emotional or behavioral problems), while 87.1% obtained normal scores on the Strengths Scale, reflecting adequate prosocial behaviors. Statistical analysis using Fisher’s Exact Test revealed a significant relationship between gadget use behavior and emotional mental disorders in children (p < 0.001). Conclusion: This study reveals a significant association between gadget use and emotional mental disorders in children in Surakarta.